Effect of irrigation-drainage unit on phosphorus interception in paddy field system. (1st April 2019) - Hua, Lingling; Zhai, Limei; Liu, Jian; Liu, Hongbin; Zhang, Fulin; Fan, Xianpeng
Abstract: In lowland agriculture, paddy fields are present in the form of irrigation-drainage unit (IDU), which consists of paddy fields and natural ditches around the fields. Phosphorus (P) export from IDUs significantly impacts water quality in adjacent water bodies. In this study, we explored the characteristics and behavior of P in a typical IDU in Jianghan Plain, China. From 2012 to 2015, we measured P concentrations in different water components of the IDU, i.e., rainwater, irrigation water, field ponding water, runoff water and ditch water, and accounted for spatial and temporal variabilities of the P concentrations. Across the rice growing season, the highest total P (TP) concentration was observed in the field ponding water. Total P concentration in ditch water gradually declined and it reached 0.06 mg L −1 at the rice maturation stage. The concentration was lower than that of incoming irrigation water (0.13 mg L −1 ) and rainwater (0.17 mg L −1 ). Although both paddy soil and ditch sediment had low degree of P saturation, the ditch sediment had greater P binding energy (1.58 L mg −1 ) and larger maximum P sorption (526 mg kg −1 ) than the soil (0.88 L mg −1 and 455 mg kg −1, respectively). The P mass balance for the rice season over the four consecutive years showed a net depletion of 3.36–8.11 kg P ha −1 yr −1 . Overall, IDUs substantially reduced the P concentrations in outputs from the IDUs as compared to inputs through irrigation and rainfall. The IDUs functioned for P retention by extending P settling time and natural degradation of P in the system. Optimizing the IDU management by controlling water discharge during fertilization and disturbance periods can be popularized for its cost saving and environmental benefits. Highlights: Paddy nutrients need to be managed at the irrigation-drainage unit (IDU) level. Prolonged water retention time in IDU helps to intercept P. Optimized IDU management makes IDU to a sink for P runoff from paddy fields. IDU can be popularized because of its cost saving and environmental benefits.